Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fphar.2020.584450
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP3 Overexpression Correlates With Poor Prognosis and Radiation Therapy Resistance in Breast Cancer

Abstract: Background: IQ motif-containing GTPase activating protein 3 (IQGAP3), the latest identified member of the IQGAP family, may act as a crucial factor in cancer development and progression; however, its clinical value in breast cancer remains unestablished. We explored the correlation between IQGAP3 expression profile and the clinicopathological features in breast cancer.Methods: IQGAP3 mRNA and protein levels were detected in breast cancer cell lines and tumor tissues by real-time PCR and western blotting and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…IQGAP3 silencing has been demonstrated to significantly reduce the proliferation, migration, and invasion ability, and induce apoptosis in pancreatic cancer cell lines ( Xu et al, 2016 ). Zhang et al found that IQGAP3 had high expression in breast cancer tissues and cell lines, and its high expression was correlated with the clinical stage, tumor node metastasis stage, and a poor prognosis ( Hua et al, 2020 ). High expression of IQGAP3 has been observed in colorectal cancer ( Wu et al, 2019 ), hepatocellular carcinoma ( Shi et al, 2017 ), bladder cancer ( Xu et al, 2019 ), and gastric cancer ( Huang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…IQGAP3 silencing has been demonstrated to significantly reduce the proliferation, migration, and invasion ability, and induce apoptosis in pancreatic cancer cell lines ( Xu et al, 2016 ). Zhang et al found that IQGAP3 had high expression in breast cancer tissues and cell lines, and its high expression was correlated with the clinical stage, tumor node metastasis stage, and a poor prognosis ( Hua et al, 2020 ). High expression of IQGAP3 has been observed in colorectal cancer ( Wu et al, 2019 ), hepatocellular carcinoma ( Shi et al, 2017 ), bladder cancer ( Xu et al, 2019 ), and gastric cancer ( Huang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…IQGAP3 is a GTPase activating protein that has been linked to fundamental cellular processes such as cell proliferation, adhesion, cytoskeletal remodelling, and growth factor regulation [ 33 ]. There has recently been an increase in the number of studies on its role in tumorigenesis of the lungs, colorectum, liver, gastric, and breast [ 33 36 ]. Surprisingly, majority of these studies suggest that IQGAP3 modulates tumorigenesis by regulating the EMT and thus controlling tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…IQGAP3 has received scant attention despite its discovery in 2007 ( 32 ) and its detection in various organs, including the liver, stomach, ovaries, prostate, breast, pancreas, and lung ( 8 , 33 38 ). IQGAP3 is mainly expressed in brain ( 39 ) and is critical for regulation of neurite outgrowth of the neurons ( 32 ).…”
Section: The Isoforms Of Iqgapsmentioning
confidence: 99%
“…Accordingly, IQGAP3 is classified as an oncogene owing to its intimate association with tumorigenesis and metastasis. Its expression is inversely linked with clinical characteristics and survival in most cancers ( 8 , 38 , 41 , 42 ).…”
Section: The Isoforms Of Iqgapsmentioning
confidence: 99%